Respuesta :
Given
y + 7 = 3x . . . (1)
6x − 2y = 12 . . . (2)
From equation (1), y = 3x - 7 . . . (3)
Putting equation (3) into equation (2) gives:
6x - 2(3x - 7) = 12
6x - 6x + 14 = 12
14 = 12 (which is not possible)
Therefore, the given system has no solution.
y + 7 = 3x . . . (1)
6x − 2y = 12 . . . (2)
From equation (1), y = 3x - 7 . . . (3)
Putting equation (3) into equation (2) gives:
6x - 2(3x - 7) = 12
6x - 6x + 14 = 12
14 = 12 (which is not possible)
Therefore, the given system has no solution.